Pemberdayaan Masyarakat Melalui Bank Sampah Dalam Meningkatkan Kesejahteraan Keluarga - Febrina Asadiya; Almisar Hamid (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This research discusses community empowerment through the Bersami Waste Bank (BSB) program. The aim of this research is to find out the process of community empowerment through the Bersami Waste Bank program in Pisangan Village, the supporting and inhibiting factors in carrying out empowerment and the Bersami Waste Bank's efforts to improve family welfare for its customers. This research is qualitative research in collecting data using observation, interviews and documentation methods. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Triangulation is used to explain the validity of the data obtained. Based on the results of this research, it can be concluded that the community empowerment carried out by the Bersami Waste Bank is in accordance with the stages of community community empowerment. The research results revealed that community empowerment through the Bersami Waste Bank was carried out through four stages, namely the awareness stage, understanding stage, utilization stage and use stage. Bersami Waste Bank can empower its community so that customers gain benefits from waste management in the form of money from savings and skills after training in waste recycling to sell from recycled waste. This is an effort by the Bersami Waste Bank to improve family welfare for its customers.